Perbandingan Kinerja Sistem Operasi Network Attached Storage: Studi Kasus Truenas dan Xigmanas - Wahyu Wijaya; Febriyanti Panjaitan; Syahril Rizal; Maria Ulfa (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Network Attached Storage (NAS) is a data storage device that operates through a computer network and provides an efficient and cost-effective storage solution due to its open-source foundation. This research compares the performance of TrueNAS and XigmaNAS as NAS operating systems in terms of data transfer speed and resource utilization over a period of 7 days. The tested parameters include file copy, file classification, file duplicate detection, CPU usage, and memory usage. The research results indicate that the average file transfer speed from server to client in TrueNAS is 7.4 Mbps, while in XigmaNAS it is 7.36 Mbps. The average file classification rate in TrueNAS is 863 files/s, whereas in XigmaNAS it is 813 files/s. The average speed of duplicate file detection in TrueNAS is 1.23 files/s, while in XigmaNAS it is 1.13 files/s. The average CPU usage in TrueNAS is 30.08%, compared to 29.38% in XigmaNAS. The average available memory for TrueNAS is 6.13 GiB, and for XigmaNAS it is 5.41 GiB. Despite the small variations and differences observed in the test results, overall, TrueNAS outperforms XigmaNAS in the analyzed aspects.